The balance of apoptotic and necrotic cell death in Mycobacterium tuberculosis infected macrophages is not dependent on bacterial virulence. - Rachel E Butler; Priscille Brodin; Jichan Jang; Mi-Seon Jang; Brian D Robertson; Brigitte Gicquel; Graham R Stewart (PLoS ONE)
Background An important mechanism of Mycobacterium tuberculosis pathogenesis is the ability to control cell death pathways in infected macrophages: apoptotic cell death is bactericidal, whereas necrotic cell death may facilitate bacterial dissemination and transmission. Methods We examine M.tuberculosis control of spontaneous and chemically induced macrophage cell death using automated confocal fluorescence microscopy, image analysis, flow cytometry, plate-reader based vitality assays, and M.tuberculosis strains including H37Rv, and isogenic virulent and avirulent strains of the Beijing lineage isolate GC1237. Results We show that bacterial virulence influences the dynamics of caspase activation and the total level of cytotoxicity. We show that the powerful ability of M.tuberculosis to inhibit exogenously stimulated apoptosis is abrogated by loss of virulence. However, loss of virulence did not influence the balance of macrophage apoptosis and necrosis--both virulent and avirulent isogenic strains of GC1237 induced predominantly necrotic cell death compared to H37Rv which induced a higher relative level of apoptosis. Conclusions This reveals that macrophage necrosis and apoptosis are independently regulated during M. tuberculosis infection of macrophages. Virulence affects the level of host cell death and ability to inhibit apoptosis but other strain-specific characteristics influence the ultimate mode of host cell death and alter the balance of apoptosis and necrosis.